Automatic flood barrier system: An approach for detection and control of storm water overflow during flood - M C Jayaprakash; Krishna Shastri C Sri; Ekaputra Rinaldi (E3S Web of Conferences)
Flooding is one of the major disasters occurring in various parts of the world. Due to the high density of buildings, flash floods are prevalent in cities. In such scenarios, there is a possibility of a drainage overflow. Therefore, implementation of an intelligent analysis of drainage leakage detection during flood using sensors are necessitated for the field of research in disaster management. The growth of Indian economy has largely affected due to flash floods. Unplanned urbanization also has a huge impact on drainage and garbage disposal system. Overflow of drainage water has become the common problem that one living in the cities usually face. To minimize the effect of drainage overflow and to alert the drainage overflow system, the paper proposes an automated mechanism. The proposed system is developed with ultrasonic sensor fitted with microcontroller to detect the overflow in the drainage system and sends an early alert warning message to the concerned authorities to take preventive measures. The implementation of proposed system at large scale will surely help to tackle the flood related issues at a larger extent.